THE IMPACT OF TIMBER HARVESTING AND TPTJ (SELECTED LOGGING AND ROW PLANTING) SILVICULTURE SYSTEM ON SOIL CARBON CONTENT POTENCY IN TROPICAL FORESTS (CASE STUDY IN IUPHHK AREAS OF PT SARI BUMI KUSUMA CENTRAL KALIMANTAN) - Almulqu A.A, Elias; Prijanto Pamoengkas (Widyariset, 2011)
Timber harvesting and TPTJ silvicultural treatment had signifi cant impact on carbon stocks in tropical natural forests. The objectives of this research were studying the impact of timber harvesting and TPTJ silvicul-tural system on carbon stock potency in the soil of tropical natural forests, and examining the characteristics of soil physical, chemical and biological properties in tropical natural forest and TPTJ logged over areas. This research was conducted in the IUPHHK of PT Sari Bumi Kusuma, Unit of Seruyan, Central Kalimantan province. Carbon stocks potency in the soil were measured in litter biomass, root biomass, and soil organic carbon, by using Brown equation (1997), where it was assumed that 50% of the biomass was carbon. Research results showed that wood harvesting and TPTJ treatment possessed signifi cant respond. Carbon stocks in TPTJ areas ranged between 93.3583–135.9631 tons of Carbon/ha, whereas carbon stock in primery forest was 122.7342 tons of Carbon/ha